Molecular docking study of ethyl acetate fraction of Selaginella doederleinii Hieron extract as anti-Warburg effect in breast cancer - Honesty N. Pinanti; Yuyun I. Christina; Muhaimin Rifa’i; Nashi Widodo; Muhammad S. Djati (Journal of Pharmacy & Pharmacognosy Research, 2023)
Context: Aerobic glycolysis is a breast cancer hallmark that has become a novel target for anticancer therapy. GLUT1, HK2, PKM2, and LDHA are oncogenic proteins in the pathway. The compounds of ethyl acetate fraction of Selaginella doederleinii Hieron extract can be developed as aerobic glycolysis inhibitors by impeding the proteins’ activity.